2009
DOI: 10.1007/s10577-009-9058-6
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the evolutionary origins of X chromosome inactivation in mammals: insights from marsupials and monotremes

Abstract: Determining the evolutionary origin of X inactivation mechanisms in mammals requires knowledge of features of X inactivation across all three major mammal lineages; monotremes, marsupials and eutherians. In the past, research into X inactivation in marsupials and monotremes lagged far behind the major advances made in understanding the mechanisms of X inactivation in human and mouse. Fragmentary knowledge of the genic content and sequence of marsupial and monotreme X chromosomes has been alleviated by the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 101 publications
(127 reference statements)
3
61
0
3
Order By: Relevance
“…Consistent with this hypothesis, XCI is limited to therian mammals with internal gestation and absent in egg-laying mammals, or monotremes (Deakin et al 2008). Furthermore, it is the paternal X that is inactivated in marsupials (Deakin et al 2009;Namekawa et al 2007). This is in contrast to most eutherians in which XCI randomly affects the maternal or paternal chromosome in the developing embryo.…”
Section: Dosage Compensation and Sex Chromosome Inactivationmentioning
confidence: 84%
See 2 more Smart Citations
“…Consistent with this hypothesis, XCI is limited to therian mammals with internal gestation and absent in egg-laying mammals, or monotremes (Deakin et al 2008). Furthermore, it is the paternal X that is inactivated in marsupials (Deakin et al 2009;Namekawa et al 2007). This is in contrast to most eutherians in which XCI randomly affects the maternal or paternal chromosome in the developing embryo.…”
Section: Dosage Compensation and Sex Chromosome Inactivationmentioning
confidence: 84%
“…Because X inactivation of the paternal X is limited primarily to marsupials, paternal imprinting of the X is considered the ancestral condition, which is maintained to a limited degree in mice, but is lost in most other eutherians (Deakin et al 2009;Namekawa et al 2007). However, genomic analyses of paternal XCI in the marsupial Monodelphis domestica (the South American opossum) and mice provide conflicting viewpoints on the evolutionary origins of paternal imprinting in mice.…”
Section: Dosage Compensation and Sex Chromosome Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…But while I was away, Des, with colleagues from Macquarie University, showed that the kangaroo X chromosome differs fundamentally from that of placental mammals in that it is always the paternal X that is inactivated, the first demonstration of imprinting in a mammal (Richardson et al 1971;Sharman 1971). Not only was the process in marsupials imprinted, but it was incomplete and tissue specific (Cooper et al 1993;Deakin et al 2009). …”
Section: Marsupial Chromosomesmentioning
confidence: 99%
“…Presently, it is thought that the mammalian Xist gene may have been derived from a protein-coding gene, Lnx3 (Duret et al, 2006), in a process that involved the insertion of transposable elements (Elisaphenko et al, 2008). Interestingly, the genomic region around the Xic shows different arrangements in placental mammals and marsupials and is autosomal in monotremes (reviewed in Deakin et al, 2009). The Xic region has undergone repeated genetic rearrangements during the evolution of mammals.…”
Section: Introductionmentioning
confidence: 99%